Influence of Deer on the Artificial Regeneration in the Mangrove of Sundarbans, Bangladesh - Siddiqi, N. A. (Indian Forester, 1996)
Studies made on the scope of artificial regeneration in the mangrove of Sundarbans, Bangladesh showed uncertain prospect due to browsing of the panted seedlings by the Spotted Deer (Axis axis). The Deer had a significant detrimental effect on the regeneration of Heritiera fornes, Xylocarpus mekongensis, Bruguiera sexangula, Ceriops decandra and Avicennia officinalis. Only Excoecaria agallocha was found to overcome the influence of Deer browsing to a large extent.